Applying Policy of South Sulawesi Architecture in Governmental Office and Public Building - PANGERAN PAITA YUNUS; SOEDARSONO SOEDARSONO; GUSTAMI GUSTAMI (Jurnal Studi Pemerintahan, 2012)
In the preservation of local culture, local government policy is required to make local regulation (Perda)which can be used as a handbook for architects and building owners, when making a plan fordevelopment in public areas but do not forget to give a typical sign of Makassar or 'raises 'traditionalarchitectural style of South Sulawesi in building offices or public buildings. South SulawesiProvincial Government's efforts to pioneer the construction of buildings or new buildings that stillemphasizes architectural Bugis-Makassar, as exemplified in 1978 by building the Office of theParliament of South Sulawesi and South Sulawesi Governor's Office, is an effort to respond positively.But these efforts did not last long. The architects, in for some time, still seems to apply the modelTimpalaja (timpanon) as a prominent feature of traditional roof Bugis-Makassar on the buildings, alsoseemed to have started to disappear from the presence of buildings or new buildings that would be anew icon for the city of Makassar.